Transient increase in neuronal chloride concentration by neuroactive aminoacids released from glioma cells - Bertollini, Cristina; Murana, Emanuele; Mosca, Luciana; D'Erme, Maria; Scala, Federico; Francioso, Antonio; Catalano, Myriam; Limatola, Cristina; Bregestovski, Piotr; Di Angelantonio, Silvia; Ragozzino, Davide (Frontiers in Molecular Neuroscience, 2012)
Neuronal chloride concentration ([Cl-]i) is known to be dynamically modulated and alterations in Cl- homeostasis may occur in the brain at physiological and pathological conditions, being also likely involved in glioma-related seizures. However, the mechanism leading to changes in neuronal [Cl-]i during glioma invasion are still unclear. To characterize the potential effect of glioma released soluble factors on neuronal [Cl-]i, we used genetically encoded CFP/YFP-based ratiometric Cl-Sensor transiently expressed in cultured hippocampal neurons. Exposition of neurons to glioma conditioned medium (GCM) caused rapid and transient elevation of [Cl-]i, resulting in the increase of fluorescence ratio, which was strongly reduced by blockers of ionotropic glutamate receptors APV and NBQX. Furthermore, in HEK cells expressing GluR1-AMPA receptors, GCM activated ionic current with efficacy similar to those caused by glutamate, supporting the notion that GCM contains glutamate or glutamatergic agonists, which cause neuronal depolarization, activation of NMDA and AMPA/KA receptors leading to elevation of [Cl-]i. Chromatographic analysis of the GCM showed that it contained several aminoacids, including glutamate, whose release from glioma cells did not occur via the most common glial mechanisms of transport, or in response to hypoosmotic stress. GCM also contained glycine, whose action contrasted the glutamate effect. Indeed, strychnine application significantly increased GCM-induced depolarization and [Cl-]i rise. GCM-evoked [Cl-]i elevation was not inhibited by antagonists of Cl- transporters and significantly reduced in the presence of anion channels blocker NPPB, suggesting that Cl-selective channels are a major route for GCM-induced Cl- influx. Altogether, these data show that glioma released aminoacids may dynamically alter Cl- equilibrium in surrounding neurons, deeply interfering with their inhibitory balance, likely leading to physiological and pathological consequences